2000
DOI: 10.1063/1.1286880
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic mechanics and the Feynman integral

Abstract: The Feynman integral is given a stochastic interpretation in the framework of Nelson’s stochastic mechanics employing a time-symmetric variant of Nelson’s kinematics recently developed by the author

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…However soon after, it was pointed out by Cameron and Daletskii [3,37,38] that a straightforward generalization does not exist, as the complex measure necessary to construct such an equivalence will have an infinite total variation. Later Pavon [39] showed that, if one considers, instead of the process (3.4), a bidirectional Nelson process defined by…”
Section: Stochastic Mechanics and The Feynman-kac Theoremmentioning
confidence: 99%
“…However soon after, it was pointed out by Cameron and Daletskii [3,37,38] that a straightforward generalization does not exist, as the complex measure necessary to construct such an equivalence will have an infinite total variation. Later Pavon [39] showed that, if one considers, instead of the process (3.4), a bidirectional Nelson process defined by…”
Section: Stochastic Mechanics and The Feynman-kac Theoremmentioning
confidence: 99%
“…An extension of the Feynman-Kac theorem to the real time path integral is given by the Feynman-Itô theorem [14,15]. Although this theorem does not have an immediate stochastic interpretation, the real time path integral has been related explicitly to the stochastic quantization framework [16].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum Mechanics (QM), including Quantum Field Theory (QFT), is the most successful mathematical framework of physical theories, with regard to its broad scope of applications and accuracy of predictions; but it is also a battle field of deep metaphysical debates. Besides the orthodox interpretation [1], [2], [3], [4], different alternative schools have appeared [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20]; to get a wide view of the present state of the art is a though undertaking (see for example [21], [22], [23], [24], [25], [26], obviously not up to date).…”
Section: Introductionmentioning
confidence: 99%